A Reliability-Based Design of Africa-Birch Timber-Reinforced Concrete Beams - Alhassan Aliyu Abdulrazaq; Uwemedimo Nyong Wilson; John Engbonye Sani; Ibrahim Rabiu (Journal of Building Materials and Structures)
This study investigates the reliability-based design of African-Birch (AB) timber-reinforced concrete beams. This study investigated Some of the physical and engineering properties of the constituent materials for the reinforced concrete beams were tested and preparing the reinforcement in four different composition and configurations (steel-steel, Steel- AB, AB-Steel, and AB-AB) of the beams were prepared, cast and cured for varying durations (3, 7, 14, 21, and 28 days), and the concrete was tested for its flexural strength and deflection and consequently  reliability analysis (in terms of  flexural strength and deflection) of all the beam configurations using First Order Reliability Analysis-5 (FORM5) to assess the beam performance was carried out. The flexural strength and deflection analysis reveals Steel-AB outperforming other sections and was found to be optimal under various loading conditions. For flexure, Steel-AB achieved a safety index (β) of 1.98 and probability of failure (Pf) of 0.0238 at a span length of 10,000mm and effective depth of 400mm. Similarly, for deflection, Steel-AB demonstrated a safety index (β) of 1.786 and probability of failure (Pf) of 0.037 at a span length of 2500mm. This study demonstrates that African-birch timber is a viable and sustainable alternative to traditional steel reinforcement for structural applications, particularly for medium span and depth beam-configurations.